House–Tree–Person Art Drawing Workshop to Improve Family Emotional Health and Reduce Divorce Risk - Hayati, Najmi (Jurnal Dedikasi Pengabdian Pendidikan, 2026)
This community service program was conducted on October 25, 2025, in Kepenuhan Hulu Village, Rokan Hulu Regency, with the participation of 20 village cadres. The program aimed to strengthen family emotional awareness and reduce the risk of marital conflict by introducing the House–Tree–Person (HTP) art-drawing technique as a reflective tool. Using a workshop format, participants engaged in guided drawing activities, small-group discussions, and facilitator-led reflections to explore emotional dynamics within family relationships. Pre- and post-session reflections were used to assess changes in participants’ understanding of emotional expression and early signs of family stress. The workshop results indicated that participants showed increased awareness of emotional cues, improved confidence in using the HTP method for community counseling, and enhanced skills in identifying potential indicators of marital strain. Participants also reported that the method was practical, culturally adaptable, and suitable for use in village-level family guidance programs. This community service activity demonstrates that creative and expressive techniques such as HTP drawing can serve as effective early-intervention tools to support family well-being and reduce the risk of divorce in rural communities.